Effects of Increased Nitrogen Deposition and Precipitation on Seed and Seedling Production of Potentilla tanacetifolia in a Temperate Steppe Ecosystem - Li, Yang (Public Library of Science, 2011)
BACKGROUND: The responses of plant seeds and seedlings to changing atmospheric nitrogen (N) deposition and precipitation regimes determine plant population dynamics and community composition under global change. METHODOLOGY/PRINCIPAL FINDINGS: In a temperate steppe in northern China, seeds of P. tanacetifolia were collected from a field-based experiment with N addition and increased precipitation to measure changes in their traits (production, mass, germination). Seedlings germinated from those seeds were grown in a greenhouse to examine the effects of improved N and water availability in maternal and offspring environments on seedling growth. Maternal N-addition stimulated seed production, but it suppressed seed mass, germination rate and seedling biomass of P. tanacetifolia. Maternal N-addition also enhanced responses of seedlings to N and water addition in the offspring environment. Maternal increased-precipitation stimulated seed production, but it had no effect on seed mass and germination rate. Maternal increased-precipitation enhanced seedling growth when grown under similar conditions, whereas seedling responses to offspring N- and water-addition were suppressed by maternal increased-precipitation. Both offspring N-addition and increased-precipitation stimulated growth of seedlings germinated from seeds collected from the maternal control environment without either N or water addition. Our observations indicate that both maternal and offspring environments can influence seedling growth of P. tanacetifolia with consequent impacts on the future population dynamics of this species in the study area. CONCLUSION/SIGNIFICANCE: The findings highlight the importance of the maternal effects on seed and seedling production as well as responses of offspring to changing environmental drivers in mechanistic understanding and projecting of plant population dynamics under global change.